Optimasi sistem kultur dan media untuk peningkatan tinggi tunas in vitro kelapa sawit - Masna Maya Sinta; Rizka Tamania Saptari; Imron Riyadi; Sumaryono Sumaryono (Menara Perkebunan, 2023)
Optimization of in vitro shoot growth is necessary to shorten the culture time and produce vigorous oil palm plantlets. This research was conducted to determine the best media and culture techniques to accelerate in vitro shoot growth of oil palm. Shoots of oil palm derived from somatic embryogenesis were grown on DF media with two culture systems (solid medium and double-layer) combined with hormone treatments (0.5-1 mg L-1 giberellin/GA3 and 0.5 mg L-1 Benzyl amino purine/BAP or thidiazuron/ TDZ). Further optimization was conducted using different bottle closures (polypropylene screw caps and plastic wraps) and macronutrients (standard or double concentrations). This research was conducted using a completely randomized design (CRD), with each treatment consisting of 5 bottle replications and each bottle consisting of 5 shoots. The results showed that media with double-layer system combined with GA3 (0.5-1 mg L-1) and TDZ (0.5 mg L-1) gave the highest shoot height increment. The use of double-strength macronutrient media combined with screw bottle caps increased shoot height (136-167 %) and decreased shoot tip necrosis (0-24 %). Plastic wrap bottle caps increased shoot tip necrosis (STN), while doubling macronutrients reduced STN. The growth of oil palm shoots began to slow down after 5 weeks of culture. In conclusion, the optimal conditions for in vitro shoot growth of oil palm were at usage of double-layer media added with GA3 0.5-1 mg L-1, TDZ 0.5 mg L-1, and double macronutrients on bottle jars with polypropylene screw caps.